2017
DOI: 10.1111/ele.12822
|View full text |Cite
|
Sign up to set email alerts
|

Boom‐bust dynamics in biological invasions: towards an improved application of the concept

Abstract: Boom-bust dynamics -the rise of a population to outbreak levels, followed by a dramatic decline -have been associated with biological invasions and offered as a reason not to manage troublesome invaders. However, boom-bust dynamics rarely have been critically defined, analyzed, or interpreted. Here, we define boom-bust dynamics and provide specific suggestions for improving the application of the boom-bust concept. Boom-bust dynamics can arise from many causes, some closely associated with invasions, but other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
183
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(186 citation statements)
references
References 91 publications
(146 reference statements)
3
183
0
Order By: Relevance
“…Although the boom‐bust phenomenon is a well‐known concept in conservation and management of non‐native invasive species, there is a lack of consensus on both its actual frequency, defining criteria and decline thresholds (Simberloff & Gibbons, ; Strayer et al., ). Based on the CPUE values observed in this study, however, it was assumed that a boom‐bust like phenomenon occurred in the black bullhead population of Lake Sava.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the boom‐bust phenomenon is a well‐known concept in conservation and management of non‐native invasive species, there is a lack of consensus on both its actual frequency, defining criteria and decline thresholds (Simberloff & Gibbons, ; Strayer et al., ). Based on the CPUE values observed in this study, however, it was assumed that a boom‐bust like phenomenon occurred in the black bullhead population of Lake Sava.…”
Section: Discussionmentioning
confidence: 99%
“…The possible causes of boom‐bust dynamics have been divided into two categories (Strayer et al., ): (a) mechanisms typically associated with invasions, and (b) general ecological mechanisms. Regarding black bullhead in Lake Sava, such dynamics probably result from an interaction between a time lag in density‐dependent populations and recovery from disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…There is a persistent idea that populations of biological invaders tend to decline steeply after an initial boom period (e.g., Simberloff and Gibbons , Strayer et al. ). Such boom–bust dynamics would be of obvious importance to management; if the severe impacts during the boom period could be tolerated or mitigated, then perhaps little or no management would be required after the population crashed.…”
Section: Introductionmentioning
confidence: 99%
“…Yet reviews by Simberloff and Gibbons () and Strayer et al. () found that population declines of established invasive species are infrequently documented owing to the scarcity of long‐term data sets, and attributing mechanisms to population declines that are observed is similarly rare. Most recently, Strayer et al.…”
Section: Introductionmentioning
confidence: 99%